Nghiên Cứu về Thực Trạng Kiểm Tra Đánh Giá Quá Trình trong Các Lớp Học Tiếng Anh tại Trường Đại Học Đông Á - Bùi Thị Hòa Oanh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The overall aims of this study are to investigate the current reality of FA in English classrooms at Dong A University. At the same time, the FA will be examined to identify how lecturers have conducted it in English classrooms, and thereby to find out some possible problems encountering when applying the FA in English classrooms at Dong A University.